Effects of the difference in ball distance on upper and lower limb movements for the overhand pass in volleyball - Nawata, R.; Ishii, Y.; Maeda, A. (Japan Journal of Physical Education, Health and Sport Sciences, 2013)
The purpose of this study was to identify the effects of different ball distances on the upper and lower limbs for the overhand pass in volleyball. Eleven male college volleyball players participated. The subjects performed the overhand pass toward objects located at three different ball distances (3, 6, and 9 m) on two force platforms, and motion analysis was performed via a motion capture system comprising 12 high-speed video cameras. The following results were obtained: (1) As the ball distance increased, the maximum dorsal flexion angular velocity of the wrist decreased, whereas the length of the pull phase, the vertical peak force on the rear leg, the maximum extension angular velocity of the hip and knee, and the maximum plantar flexion angular velocity of the ankle all increased. Therefore, adjustment of the ball distance for the overhand pass was facilitated by changing the impulse of the ball caused by increasing the intensity of both the rear leg step and the wrist stiffness. (2) In the previous instructional manual, the buffer action for the falling ball during overhand passing was facilitated by flexion of the whole body. However, in this study, the buffer action was facilitated conducted only with the upper limb irrespective of the ball distance. From the viewpoint of the series of movements during overhand passing, the whole body was used in the period from flexion to extension, but the flexion action of the whole body was incorporated into the preparatory phase, and the buffer did not involve the lower limbs after ball contact. This difference between the previous instructional manual and the present findings are attributed to the imprecise definition of movement phases in the manual.